2009
DOI: 10.1161/circresaha.109.201418
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Plakophilin-2 Expression Leads to Decreased Sodium Current and Slower Conduction Velocity in Cultured Cardiac Myocytes

Abstract: Key Words: plakophilin-2 Ⅲ intercalated disc Ⅲ arrhythmogenic right ventricular cardiomyopathy Ⅲ cardiac desmosomes A high-resolution image of the site of end-end contact between cardiomyocytes reveals an electron-dense organization called "the intercalated disc." Its classic definition involves 3 structures: desmosomes and adherens junctions, providing mechanical coupling; and gap junctions, allowing electric/metabolic synchronization between cells. Recent studies show that other molecules, not directly invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
258
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 283 publications
(279 citation statements)
references
References 7 publications
19
258
1
1
Order By: Relevance
“…In the intercalated disc (ID) region, Na V 1.5 colocalizes with N‐cadherin, ankyrin G, plakophilin‐2, and synapse‐associated protein 97, whereas Na V 1.5‐based channels located at the lateral membrane (LM) of the cardiomyocyte associate primarily with the dystrophin‐syntrophin complex 8, 9. Remodeling of region‐specific proteins may affect Na V 1.5 locally and lead to disturbances in I Na , conduction abnormalities, and arrhythmias 10, 11, 12, 13…”
mentioning
confidence: 99%
“…In the intercalated disc (ID) region, Na V 1.5 colocalizes with N‐cadherin, ankyrin G, plakophilin‐2, and synapse‐associated protein 97, whereas Na V 1.5‐based channels located at the lateral membrane (LM) of the cardiomyocyte associate primarily with the dystrophin‐syntrophin complex 8, 9. Remodeling of region‐specific proteins may affect Na V 1.5 locally and lead to disturbances in I Na , conduction abnormalities, and arrhythmias 10, 11, 12, 13…”
mentioning
confidence: 99%
“…13 Experimental and clinical data suggest that other non-junctional cellular structures like the voltage-gated sodium channel (Nav 1.5), the sarcolemmal calcium channel regulating molecule PLN, and structural molecules are linked to desmosomes. 14 Especially PLN phosphorylation has been reported to play a key role in the pathophysiology of heart failure. 15 Taken together, various cellular pathways, particularly electromechanical cell-to-cell coupling, inflammation, apoptosis, adipogenesis and fibrosis seem to be involved in the pathophysiology of ARVC/D, but the interactions are not fully understood.…”
mentioning
confidence: 99%
“…In the latter it is necessary for heart formation and for the onset and coordination of rhythmic heart beat, 18,[44][45][46][47][48] be it directly or indirectly (for further involvements of sodium channels or gap junctions, see also recent knockdown experiments). [49][50][51][52] Most impressive in the discussions about possible functional roles of Pkp2 are certainly the recent reports that cardiac Pkp2 is by far the most sensitive protein, which in mutated forms can contribute to arrhythmogenic ventricular cardiomyopathies (ARVCs). [46][47][48][49][50][51][52][53] Moreover, in Pkp2 gene knockdown experiments, it has also been shown that its stabilizing effect on cell-cell adhesion in rat cardiomyocyte cultures is so important that a reduction in Pkp2 can result in a complete separation of the two junctional membranes.…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48][49][50][51][52][53] Moreover, in Pkp2 gene knockdown experiments, it has also been shown that its stabilizing effect on cell-cell adhesion in rat cardiomyocyte cultures is so important that a reduction in Pkp2 can result in a complete separation of the two junctional membranes. [49][50][51][52] Thus, in myxoma tumors growing in a very viscous, mucoid-gelatinous matrix, the acquisition of Pkp2 to the adherens junctions may have an important stabilizing effect and strengthen cell-cell adhesions, in particular those connecting the long and thin cell processes.…”
Section: Discussionmentioning
confidence: 99%